Triptych - Slaughter, Karin (New York : Delacorte Press, 2006)
From Atlanta$1 (Bs wealthiest suburbs to its stark inner-city housing projects, a killer has crossed the boundaries of wealth and race. And the people who are chasing him must cross those boundaries, too. Among them is Michael Ormewood, a veteran detective whose marriage is hanging by a thread$1 (Band whose arrogance and explosive temper are threatening his career. And Angie Polaski, a beautiful vice cop who was once Michael$1 (Bs lover before she became his enemy. But unbeknownst to both of them, another player has entered the game: a loser ex-con who has stumbled upon the killer$1 (Bs trail in the most coincidental of ways$1 (Band who may be the key to breaking the case wide open.s
88455
Keywords: Serial murderers -- Fiction; Atlanta (Ga.) -- Fiction; Psychological fiction; Suspense fiction